Strategic role of Indian State Agricultural Universities (SAUs) in rural development: A review - Lalitha, A.; Purnima, K. S.; Reddy, K. Gurava; Babu, Suresh Chandra; Sambaiah, A. (Agricultural Research Communication Center, 2022)
State Agricultural Universities (SAUs), in India, have adopted the U.S. land-grant model to meet its goals. They are autonomous organisations with state-wide responsibility for agricultural education, research and extension education. Through teaching, research and extension activities the 64 SAUs across 28 states of India are significantly contributing to agricultural production and productivity of their respective states directly and therefore to the rural development. SAUs rural development strategies include technologies and innovations, extension and human resource development. Regional Agricultural Research Stations in various agro-climatic zones have strengthened research-extension-farmer (REF) linkages. KVKs under administrative control of SAUs serve as farm science centres of their respective districts. In this paper, the rural development approaches of Acharya N.G. Ranga Agricultural University, Guntur Andhra Pradesh is detailed. Furthermore, strategic planning by the SAUs to increase their effectiveness for direct rural development should be sustained.